STEM-07. DEFINING THE ROLE OF HUMAN ENDOGENOUS RETROVIRUS-K (HML-2) IN THE GLIOBLASTOMA STEM-CELL NICHE. (14th November 2022) - Shah, Ashish; Rivas, Sarah; Doucet-Ohare, Tara; Govindarajan, Vaidya; DeMarino, Catherine; Ampie, Leo; Banasavadi-Siddegowda, Yeshavanath; Maric, Dragan; Garcia-Montojo, Marta; Suter, Rob; Lee, Myoung-Hwa; Walbridge, Stuart; et al.
Abstract: Human Endogenous Retrovirus (HERV) are ancestral viral relics that comprise nearly 8% of the human genome. Although silenced in normal tissues, the most recently integrated provirus HERV-K (HML-2) can be pathologically reactivated in certain cancers. Here, we report pathological expression of HML-2 transcripts in human malignant gliomas in cerebrospinal fluid (HERV-K DNA/RPP30=35.2±8.8 vs 23.1±6.7, n=18, p=0.02) and tumors (HERV-K RNA/HPRTmean=1.15±0.2 vs. 0.5±0.2, p=0.01, n=20) compared to epilepsy controls. Aberrant HML-2 expression corresponded to a unique stem-cell niche using multivoxel automated segmentation. Using a tailored single-cell RNA sequencing pipeline to detect retrotransposons, we identified glioblastoma cellular populations with elevated HML-2 transcripts in neural progenitor-like cells that can drive cellular plasticity (ANOVA, multiple-testing correction, p< 0.001). Using CRISPR technology, we demonstrate that HML-2 is critical to maintenance of glioblastoma stemness and tumorigenesis in both glioblastoma neurospheres and intracranial orthotopic murine models (OS: 26 days vs. 18.6, p=0.0008, n=20). Downregulation of HERV-K using CRISPRi reduces the glioblastoma neurosphere formation (2-way ANOVA, p< 0.0001). and HERV-K env, Polymerase, OCT4 and Nestin transcripts (2-way ANOVA p< 0.001). Using Chromatin Immunoprecipitation, we determined that this interaction in gliomas is likely mediated by the nuclear transcription factor OCT4 which binds to an HML-2 specific Long-Terminal Repeat (LTR5Hs). Moreover, using Transmission Electron Microscopy, we discovered that some glioma stem-cells form immature retroviral virions in glioblastoma. Inhibiting HML-2 expression with nucleoside reverse transcriptase inhibitors reduces extracellular reverse transcriptase (One-way ANOVA, p< 0.05), tumor viability (IC50=75.8-123.1 uM), and pluripotency (One-way ANOVA, p< 0.01). Our results suggest that HML-2 is overexpressed in the cancer stem-cell niche of glioblastoma. Since persistence of glioblastoma stem-cells is considered responsible for treatment resistance and recurrence, HML-2 may serve as a unique therapeutic target in glioblastoma.